The Knowledge Map of Sport and Exercise Psychology: An Integrative Perspective - Latinjak, Alexander T.; Hatzigeorgiadis, Antonis (Frontiers in Psychology, 2021)
The present work contains a personal perspective on what sport and exercise psychology (SEP) is today. It is a global synthesis of research about psychological aspects related to the context and practice of sport and exercise. The intended impact was to positively influence teaching SEP to students, to promote interdisciplinary research and practice, and to assist the development of SEP as an applied science by helping experts develop a more holistic view of the field. Over 650 theoretical and review articles about psychological concepts in connection to sport and exercise were read in the process of creating a conceptual model that reflects the essence of SEP and leads to a conceptualization of SEP based on research topics. The result was a knowledge map of SEP made up of four main research clusters: biopsychological descriptors, external variables, psychological skills, and applied SEP practice. In terms of interdisciplinarity, the present perspective on SEP suggests that sport and exercise can be used as a research paradigm or natural laboratory to study psychological aspects relevant to various scientific fields, and that sport and exercise can be used as a therapeutic framework in response to challenges that researchers and practitioners in these fields are typically addressing.